2019
DOI: 10.1101/863514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nucleus acts as a ruler tailoring cell responses to spatial constraints

Abstract: The microscopic environment inside a metazoan organism is highly crowded. Whether individual cells can tailor their behavior to the limited space remains unclear. Here, we found that cells measure the degree of spatial confinement using their largest and stiffest organelle, the nucleus. Cell confinement below a resting nucleus size deforms the nucleus, which expands and stretches its envelope. This activates signaling to the actomyosin cortex via nuclear envelope stretch-sensitive proteins, upregulating cell c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Here we propose that tumor growth associated with the formation of peripheral motile strands of cells leads to strong deformation of the nucleus at the tumor edges. Nuclear deformation has been associated with several pathways ( 53 ), either triggering immediate cellular response, for example leading to an increase in cell contractility and motility ( 54,55 ), or to longer term responses associated with changes in gene expression and overall cell state or fate ( 56 ). Nuclear deformation was also shown to trigger YAP entry into the nucleus ( 57 ), and to trigger G1/S transition ( 58 ), thus potentially favoring cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we propose that tumor growth associated with the formation of peripheral motile strands of cells leads to strong deformation of the nucleus at the tumor edges. Nuclear deformation has been associated with several pathways ( 53 ), either triggering immediate cellular response, for example leading to an increase in cell contractility and motility ( 54,55 ), or to longer term responses associated with changes in gene expression and overall cell state or fate ( 56 ). Nuclear deformation was also shown to trigger YAP entry into the nucleus ( 57 ), and to trigger G1/S transition ( 58 ), thus potentially favoring cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the better known mechanisms of mechanotransduction in adherent cells (which often involve Src), cells may use different mechanisms for sensing confinement 31 . This idea is supported by recent evidence that the INM unfolds and activates a cytosolic Phospholipase A2 (cPLA2)-dependent mechanotransduction pathway in confined cells, increasing actomyosin contractility 12,13 .…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, this phenotypic transition has been found to be promoted by cell confinement 7,8,10,11 . Although compressing the cell (i.e., confinement) may be sufficient to pressurize the cytoplasm, recent studies have suggested that cells adapt to confinement by upregulating actomyosin contractility 12,13 . Because of this dependence on confinement, rapid LBBM is likely to require the precise tuning of cell stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Opisthokont ancestors might have crawled using a combination of blebs (as in amoeboid choanoflagellates, amoeboid animal cells 9,11 , and amoebozoans 44 ), pseudopods (which are present in choanoflagellates during phagocytosis 22,39 and during crawling in chytrid fungi 8,39 , amoebozoans 44 , and some holozoans 38 ), and filopodia (which contribute to locomotion in filastereans 63 and choanoflagellate settlement 30 ). Moreover, cell crawling is regulated by confinement in animal cells 912 , choanoflagellates, chytrid fungi 39 and dictyostelid amoebozoans 44 , suggesting that the ability to respond to confinement might be an ancient feature. These prior findings, together with our observation of an amoeboid switch in choanoflagellates, suggest that the switch from a flagellate to a crawling phenotype in response to confinement was part of an ancestral stress response in the last common choanozoan ancestor 74 .…”
mentioning
confidence: 99%
“…4p). However, the ancient response to confinement was not necessarily fully lost – as confinement activates blebbing in vertebrate mesenchymal and embryonic cells 9,11 through a transduction pathway that makes use of newly evolved proteins, such as the phospholipase cPLA2 10,12 that does not exist in choanoflagellates 21,75 .…”
mentioning
confidence: 99%